Recombinant expression of the Aryl Hydrocarbon Receptor - Shaikh-Omar, Osama (2007)
Aryl Hydrocarbon Receptor (AhR) mediates drug and toxin action. The AhR proteins have been characterised in several mammalian species, and are soluble proteins found in various tissues. The AhR is normally found in the cytoplasm in a complex with 90 KDa heat shock protein (hsp90) and cellular chaperones such as ARA9 (AIP or XAP2) and p23. However, there has not been a systematic analysis of the proteins which chaperone the AhR ligand-binding domain (LBD). This work investigates the interaction between ligands and the AhR, the protein composition of the AhR ligand-binding domain (LBD) complex, by establishing translation of AhR LBD in reticulocyte lysate, which contains molecular chaperones such as hsp90, and p23 that stabilise the ligand binding form of AhR.